KEEFEKTIFAN KONSELING KELUARGA TERHADAP PEMBERANTASAN DEMAM BERDARAH DENGUE - -, Nasrudin; Mukarromah, Indah (Eduhealth, 2010)
AbstractDengue Hemorrhagic Fever (DHF) remains a serious public health concern in Indonesia. Almost throughout the country have been affected by this disease. Sragen district is one of the areas in Central Java that had DHF incidence of 3.24/ 10,000 people and case fatality rate of 1.45% in 2006. Various control measures have been implemented such as group education, breeding place elimination, abatisation, and focus fogging. The results, however, have not been satisfactory. Counseling is one of family approaches that aims to enhance community understanding and to find the best soution to problems. This study was a Randomized Controlled Trial, conducted in Jogoroto subdistrict, Sragen. The study subjects included 60 families that were selected by purposive sampling whose houses were identified to have Aedes aegypti larvae. The inclusion criteria were families who resided in the houses for at least a year, and were identified to have larvae in the house and the yard. The exclusion criteria were families who planned to move or elderly who lived alone during the study period. The data was analyzed by use of t and Chi Square testsThe study results showed that the family counseling significantly increased knowledge (t=3.39; p=0.001), attitude (t= 7.22; p=0.000), and practice (t=2.91; p=0.005). Family counseling also reduced the presence of Aedes aegypti larvae (X2=20.81; p=0,000). The study concludes that family counseling is effective in improving knowledge, attitude, and practice of the community in DHF control. It is recommended that the District Health Office adopt family approach such as counseling so as to bring about better behavior for the DHF control. Keywords: family counseling, dengue hemorrhagic fever control